2008
DOI: 10.1109/jsen.2008.2006471
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent ISFET Sensory System With Temperature and Drift Compensation for Long-Term Monitoring

Abstract: This paper presents a new intelligent ISFET sensory system dedicated to a precision pH sensory function, as well as a long-term monitoring capability without being jeopardized by temperature and drift fluctuations in the water-quality monitoring environment. It includes the novel compensation technique for counteracting a simultaneous change of temperature and drift, the design of the sensory system incorporating hardware and software co-design for enhancing the performance stability of a standard ISFET device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…The double layer capacitance C DL consists of the two series capacitances C Gouy and C Helm , where C Gouy represents the equivalent Gouy-Chapman capacitance and C Helm the Helmholtz capacitance, which has already been developed by site-binding theory and the electrical double-layer theory [17,18]. It should be noted that C Gouy and C Helm are temperature dependent, however, since these are second-order effects, we will assume C Gouy and C Helm to be independent of temperature [5]. Thus, it has been possible to investigate the pH-ISFET flat-band voltage shift with pH and the variation of the potential at the electrolyte/gate dielectric interface.…”
Section: Isfet Electrical Properties: Background Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The double layer capacitance C DL consists of the two series capacitances C Gouy and C Helm , where C Gouy represents the equivalent Gouy-Chapman capacitance and C Helm the Helmholtz capacitance, which has already been developed by site-binding theory and the electrical double-layer theory [17,18]. It should be noted that C Gouy and C Helm are temperature dependent, however, since these are second-order effects, we will assume C Gouy and C Helm to be independent of temperature [5]. Thus, it has been possible to investigate the pH-ISFET flat-band voltage shift with pH and the variation of the potential at the electrolyte/gate dielectric interface.…”
Section: Isfet Electrical Properties: Background Reviewmentioning
confidence: 99%
“…Commercially available sensors are generally very expensive devices, especially if reasonable precision and reliability are requested. Several investigations have demonstrated that the pH-ISFET sensor presents some drawbacks related to thermal dependency and long-term drift [4][5][6]. These factors limit the performances of pH-ISFET sensors, leading to unacceptable results in critical measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Casans et al (2004) showed an instrumentation system designed to compensate long-term drift on ISFETs. Smart compensation (Chen and Chan, 2008) is processed by two approaches: 1 It utilizes a dynamic biasing current temperature compensation technique to provide optimum biasing current for ISFET dynamically. This results in an almost zero temperature coefficient for nonlinear biasing point at different pH values.…”
Section: Discrete Mosfet Segment Ph-sensitive Componentmentioning
confidence: 99%
“…ISFETs have to be calibrated over a period of time to compensate for the drift in the threshold voltage. Several methods have been used to compensate for the drift [12] [13] [14]. Our group previously reported a new method to mitigate drift.…”
Section: Introductionmentioning
confidence: 99%